The Problem of Giving Sense to the Teachers Profession is a Point of Reference to Professional Skill Development - Stančikaitė., Regina (Acta Paedagogica Vilnensia, 2002)
For the successful educational reform it is important to have an attentive ear to the teacher’s problems, their expectations, to respect them as well as give scientific assistance for mating their profession meaningful. We felt absence of the works, analysing the functioning of values in the teacher’s professional activity, their ties with the process of giving meaning to this profession. Referring to the analysis of scientific literature and the results of phenomenological investigation the principal components of giving sense to the teacher’s profession were revealed: concept of professional values, peculiarities of professional experiences tendencies of realization of professional values, self-esteem of teacher’s workmanship. Understanding of pedagogical work values and professional competence reveal the concept of professional values. The individuality of professional experiences is highlighted by the teacher’s satisfaction with their professional activity, by emotional evaluation of the teacher’s profession and of pupils, by other feelings and emotions, dominating in pedagogical work. The teacher’s pedagogical troubles and goals of pedagogical activity show the tendencies of realization of professional values. Self-esteem of teacher’s workmanship manifests itself by the evaluation of the achieved professional level. The investigation revealed the teacher’s giving sense to their profession – their general system of values and professional perfection. The background of the general system of values is made up of humanistic and belief in God values.